Strategic Design of Information System Implementation at University - Darmalaksana, Wahyudin; Ali Ramdhani, Muhammad; Cahyana, Rinda; Syakur Amin, Abdusy (International Journal of Engineering and Technology, 2018)
Higher education over the past decade has experienced several view changes that include: paradigm shift, management and competition changes, and so forth. The only university supported by the excellent IT that will be able to enhance and maintain its advantages. The purpose of this article is reviewing the strategic design of IT implementation at the university.Â The analysis used to reveal the fact, problem and problem-solving in this article adopts the model of Strategic Management of Information Technology (SMIT) developed by FlodstrÃ¶m.Â The strategy design of IT implementation based on the competitive environment of UIN Sunan Gunung Djati Bandung is coordinated with its business strategy. The role of IT as an enabler or tool that allow the university to be able to create cheaper-better-faster educational process. In this article, there are designed two types of IT Functions: back office and front office. For back office application function, there is a software management with specific modules to support the implementation of university management. In the front office function of IT usage, there are some types of IT usage concepts that directly and indirectly affect the way of establishing education that leads to quality improvement which can be implemented through: media simulation, course management, virtual class, computer-based training (CBT), knowledge portal and cyber community.Â The strategic design of IT implementation presented in this article is a generic model of the plan, design, and implementation of IT in the object of study.Â Â